2010
DOI: 10.14723/tmrsj.35.191
|View full text |Cite
|
Sign up to set email alerts
|

Tight Bonding between Two Sheets of Biaxially Oriented Polyester Induced by Exposure to Oxygen-Implicated Plasma

Abstract: Biaxially oriented polyethylene terephthalate (PET) films were exposed to oxygen-implicated plasma. They were pressed at 100℃ with their exposed surfaces faced, then bonded tightly without using glue. X-ray photoelectron spectroscopy showed increase in C=O group at the exposed surface, and gas chemical modification method showed increases in-OH and-COOH groups. They might indicate that a mechanism of the two-sheets bonding is related to hydrogen bond or condensation reactions concerning these functional groups. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…FTIR-ATR spectrum around 1716 cm -1 for the nonirradiated sample (100μm) is shown in Figure 5. This peak arises from C=O bond included in the original PET material [3]. After the irradiation the absorption is increased around 1711 cm -1 (see an inset).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…FTIR-ATR spectrum around 1716 cm -1 for the nonirradiated sample (100μm) is shown in Figure 5. This peak arises from C=O bond included in the original PET material [3]. After the irradiation the absorption is increased around 1711 cm -1 (see an inset).…”
Section: Resultsmentioning
confidence: 94%
“…Sample size is 100 mm x 200 mm, and thickness is 1 μm and 100 μm. The film samples were attached on a grounded drum electrode in a vacuum chamber [3]. The chamber was evacuated down to 10 Pa, then O 2 gas was introduced with 20 cc/min to 40 Pa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have to collect the organic solvents in used lamination processes, because they cause environmental problems. 12) We demonstrated the direct bonding between PET and PET, [13][14][15][16] and PET and other plastic films 4) by a plasma irradiation technique and low thermal press 5,[13][14][15][16] without using any glues. The bonding force is stronger than the film cohesion force, as demonstrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The bonded films have peel strengths larger than 10 N/cm in the 180°peel test, beyond which they show cohesion failure. 5,13) We propose that the mechanism of bonding involves dehydrated condensation reactions between the plasma-created active OH and COOH groups 17,18) at the interface of two irradiated films under the low temperature press. [13][14][15][16] It was found that this plasma irradiation effect on bonding capability can be maintained for more than six years when the irradiated films are kept in the normal atmosphere.…”
Section: Introductionmentioning
confidence: 99%